EVALUASI IMPLEMENTASI PPDB ZONASI DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI SMPN 107 JAKARTA - kasiati kasiati; hery muljono; erna kusumawati (Universitas Pendidikan Indonesia, 2021)
This study aimed to evaluate the implementation of the zoning PPDB in improving the quality of education at SMPN 107 Jakarta. Data were collected using observation, interview and documentation techniques with the Countenance Stake model. Qualitative descriptive analysis technique through QSR NVivo 12 software. The results of the study were: (1) The antecedent component showed a match between the availability of PPDB policy tools at SMP Negeri 107 and the policy in the DKI Jakarta Government. The availability of facilities both online and offline had been fulfilled. It was necessary to improve the stability of internet by reviewing the providers used. Criteria based on capacity with age selection. The change in the determination of the capacity from 36 changes to 40 students per study group. Zoning was determined by using district and subdistrict; (2) The transaction component showed that the PPDB mechanism and process at SMPN 107 was in standard with Kepdis No. 501/2020. PPDB was carried out online through the ppdb.jakarta.go.id site. There was server problems and unstable internet networks; (3) the outcome component of the decline in the quality of student learning achievement. Heterogeneous characteristics of students made competition between students less optimal, resulting in decreased learning enthusiasm.